Enhancing Soil Health With Cover Crops - Strauss, Sarah; Castellano-Hinojosa, Antonio; Kadyampakeni, Davie; Kanissery, Ramdas; Wade, Tara (EDIS, 2020)
Soil health is generally synonymous with soil quality and refers to the capacity of a soil to sustain biological productivity, maintain environmental quality and promote plant health. Soils are complicated ecosystems, and discussions of soil health must consider the links between soil functions and soil-based ecosystem services, such as crop production, erosion control, pest and disease control, and biodiversity conservation. Peer reviewed through UF/IFAS Citrus Research and Education Center; published in Citrus Industry Magazine.